2021
DOI: 10.7554/elife.64977
|View full text |Cite
|
Sign up to set email alerts
|

Unique integrated stress response sensors regulate cancer cell susceptibility when Hsp70 activity is compromised

Abstract: AMPK, AMP-activated protein Kinase; AKT, AK strain Transforming serine/threonine kinase; ASNS, asparagine synthetase; ATF4, activating transcription factor 4; ATF6, activating transcription factor 6; BiP, Immunoglobulin Binding Protein; CHOP, C/EBP homologous protein; CQ, chloroquine; DTT, 1,4-Dithiothreitol; EBSS, Earle's balanced salt solution; eIF2α, eukaryotic initiation factor 2 alpha; ER, endoplasmic reticulum; ERAD, endoplasmic reticulum associated degradation; FBS, fetal bovine serum; GCN2, general con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 196 publications
(317 reference statements)
0
12
0
Order By: Relevance
“…However, unexpectedly, HSP70 levels were markedly reduced by 2-DG treatment in the resistant HCTR cells only. This selective decrease of HSP70 in cells with acquired BOLD-100 resistance indicates a generally disturbed proteostasis [65,80] induced by BOLD-100 selection and, thus, provides another explanation for the observed hypersensitivity of resistant cells towards 2-DG treatment. HSP70, as a central protein fate hub, is known to be implicated in several protein degradation pathways, including, amongst others, micro-, macro-, or chaperone-mediated autophagy [81].…”
Section: Discussionmentioning
confidence: 82%
“…However, unexpectedly, HSP70 levels were markedly reduced by 2-DG treatment in the resistant HCTR cells only. This selective decrease of HSP70 in cells with acquired BOLD-100 resistance indicates a generally disturbed proteostasis [65,80] induced by BOLD-100 selection and, thus, provides another explanation for the observed hypersensitivity of resistant cells towards 2-DG treatment. HSP70, as a central protein fate hub, is known to be implicated in several protein degradation pathways, including, amongst others, micro-, macro-, or chaperone-mediated autophagy [81].…”
Section: Discussionmentioning
confidence: 82%
“…A chaperone-mediated protein degradation pathway, is upregulated in bortezomib (Bz)-resistant multiple myeloma (MM) cells, accompanied with increased levels of lysosomal associated membrane protein 2A (LAMP2A), the rate-limiting factor of the CMA pathway; the inhibition of CMA sensitizes resistant cells to Bz 162 . Recent studies showed that HSP70 inhibition in resistant breast cancer cells might enhance autophagy and chemoresistance 163 . Autophagy has higher levels in most drug resistant cells, and was highest only in drug resistant cells upon HSP70 inhibition 163 .…”
Section: Mechanisms For Regulation Of the Mdr-associated Factors Or S...mentioning
confidence: 99%
“…Therefore, tumor progression needs proteostasis adjustment by the upregulation of ATF4 and the modulation of cellular stress responses. Recent investigation suggests that GCN2-mediated autophagy prevents proteotoxicity in breast cancer cells and demonstrates complementary mechanisms to ensure survival [ 150 ]. ATF4 or GCN2 expression abrogation significantly inhibited tumor growth in MEFs [ 60 ].…”
Section: Integrated Stress Response (Isr)mentioning
confidence: 99%